Bulk effects on topological conduction in three-dimensional topological insulators - Wu, Quansheng (2014)
The surface states of a topological insulator in a fine-tuned magnetic field are ideal candidates for realizing a topological metal which is protected against disorder. Its signatures are (i) a conductance plateau in long wires in a finely tuned longitudinal magnetic field and (ii) a conductivity which always increases with sample size, and both are independent of disorder strength. We numerically study how these experimental transport signatures are affected by bulk physics in the interior of the topological insulator sample. We show that both signatures of the topological metal are robust against bulk effects. However the bulk does substantially accelerate the metal's decay in a magnetic field and alter its response to surface disorder. When the disorder strength is tuned to resonance with the bulk band the conductivity follows the predictions of scaling theory, indicating that conduction is diffusive. At other disorder strengths the bulk reduces the effects of surface disorder and scaling theory is systematically violated, signaling that conduction is not fully diffusive. These effects will change the magnitude of the surface conductivity and the magnetoconductivity.